[tex]a = 0,125 - \frac{1}{2} : 1\frac{1}{3}[/tex]
[tex]a = \frac{1}{8} - \frac{1}{2} * \frac{4}{3}[/tex]
[tex]a = \frac{1}{8} - \frac{4}{6}[/tex]
[tex]a = -\frac{1}{2}[/tex]
[tex]b = (-\frac{2}{3})^{2} - \frac{1}{3}[/tex]
[tex]b = \frac{4}{9} - \frac{1}{3}[/tex]
[tex]b = \frac{1}{9}[/tex]
[tex]c = \frac{1}{2} - \frac{2}{5} * \frac{5}{4}[/tex]
[tex]c = \frac{1}{2} - \frac{1}{2}[/tex]
[tex]c = 0[/tex]
[tex]d = \frac{4+(-12)}{-2} + \frac{(-3)^{3} }{7-(-2)}[/tex]
[tex]d = -\frac{8}{2} + -\frac{27}{9}[/tex]
[tex]d = -4 - 3[/tex]
[tex]d = -7[/tex]
Odp: C